Faktor-Faktor Yang Berhubungan Dengan Perilaku Seksual Remaja Di Kabupaten Bulukumba - Arfiani Arfiani; Husnul Khatimah; Kurniati Akhfar (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Based on 2013 BKKBN data, the number of sexual behaviors among adolescents aged 14-19 years reached 41.8 percent. This research aims to determine the factors related to sexual behavior in adolescents at SMA Negeri